Landslide Vulnerability-Based Disaster Mitigation Planning in the Elementary School Environment, Boyolali Regency - Hidayah, Kuny; Azizah, Novita Nur; Hamid, Fauzia Rahman; Aqimuddin, Muchammad Alfa; Ahmad, Radix Dzakiya; Wibowo, Yunus Aris (Universitas Pendidikan Indonesia, 2021)
Landslide is a disaster that potentially harmful to the community. Education facilities are severely vulnerable to landslides. Therefore, this study focused on analyzing the environmental vulnerability of elementary education in landslides-prone area (KRB) in Boyolali Regency as a basis for disaster mitigation planning. The population in this study were all primary schools in landslides-prone area (KRB) of Boyolali Regency. The sampling technique was conducted by using purposive sampling. The school sample was determined based on the location in the landslides-prone area (KRB) of Boyolali Regency, the location of the school based on the slope, and the similarity of Accreditation from the Indonesian Ministry of Education and Culture. Respondents in this study were the principal and permanent teachers in each sample school. The data analysis in this research was done by using descriptive statistics. The analysis of the vulnerability of elementary education was obtained from the results of questionnaires and interviews which have been validated by field survey. These results were used as the basis for landslide disaster mitigation planning. The indicators of vulnerability in this study are policies, facilities and infrastructure, knowledge, and structure of school buildings. The results of data analysis showed that the three sample schools belonged to three different vulnerability classes. The findings in this study are the level of vulnerability of the elementary education environment was not in line with the location of the school in the landslides-prone area (KRB) of Boyolali Regency and the slope. SDN 1 Ngadirojo was located on a gentle slope but had a high level of vulnerability because of low preparedness. SDN 2 Jlarem was on a rather steep slope with a moderate level of vulnerability because of its good preparedness. Furthermore, SDN 2 Ngagrong was on a steep slope but had high preparedness so that its level of vulnerability was low